In vitro digestibility of rare sugar (D‐allulose) added pectin–soy protein gels. (8th April 2021) - Ates, Elif Gokcen; Ozvural, Emin Burcin; Oztop, Mecit H.
Summary: Confectionery gels are known to be high‐caloric products due their high sugar content. Changing their formulations by substituting the sugar with alternative natural sweeteners and functionalising them, the addition of proteins has gained attention. Understanding the rate of digestion of these products is also important for selecting the appropriate formulation. In this study, in vitro gastric digestion behaviour of the gels formulated with D‐allulose, a low‐calorie rare sugar, soy protein isolate (SPI) (1%, 2.5%) and pectin (4%) were examined. Digestion decreased the hardness of the gels ( P  < 0.05), but, at 2.5% SPI concentration. Moisture content of the samples increased after digestion and presence of SPI induced higher water uptake. At the end of 2 h of digestion, 1% soy protein isolate containing gels had the highest brix values showing that after a certain concentration, soy protein isolate governed the system due to improved soy protein–pectin interaction or due to improved gelation with Maillard reaction. NMR relaxometry experiments further confirmed the changes in the gels with the increase in T 2 values. Power law model was fitted for the dissolution behaviour using the o Brix values of the digestion medium. Dissolution of sugar and the contribution of SPI to the gel network were clearly observed in SEM images. Results showed that these gels had the potential to slow down the emptying rate of stomach thus could lead to 'fullness' for a longer time. Abstract : D‐Allulose and soy protein isolate containing pectin gels were prepared to be digested in mouth and gastric medium. Scanning Electron Microscopy; Nuclear Magnetic Resonance Relaxometry; Texture Profile Analysis experiments were performed for the gels before and after digestion and Brix values of the gastric medium were measured to understand the digestion kinetics.